Exploring the effectiveness of local content requirements in promoting solar PV manufacturing in India - Oliver Johnson (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
In a bid to make renewable energy technology deployment strategies politically acceptable, many countries are linking them to socio-economic goals, such as job creation, economic development and building competitiveness. A controversial industrial policy tool that is becoming increasingly popular is the use of local content requirements (LCRs). These regulate the extent to which certain projects must use local products and are often justified on the basis of supporting local employment and private sector development. The debate has centred around the rights and wrongs of protecting infant industry, with little progress being made to find a common ground. This paper seeks to move beyond this stalemate to understand under which conditions LCRs might be a legitimate and effective tool for promoting local manufacturing. To do so, it applies an effectiveness framework to LCRs for solar photovoltaics in India's National Solar Mission. The paper finds that for LCRs to be effective, they must be (a) limited in duration and incorporate planned evaluation phases, (b) focused on technologies and components for which technical expertise is available and global market entry barriers are manageable, (c) linked to additional mechanisms, such as training and promotion of business linkages and measures to support other stages of the value chain and wider services that are integral to success of renewable energy industries.
Keywords: 330